Development of a Smart Game Application for Auditory Training of Children with Spatial Processing Disorder in Iran: A Pilot Study. - Tajik, Sima; Ghahraman, Mansoureh Adel; Farahani, Saeid; Rouhbakhsh, Nematollah; Taheri, Alireza; Bahramsari, Parsa; Jalaie, Shohreh (Auditory & Vestibular Research (2423-480X), 2024)
Background and Aim: Identifying sound localization defects in children and using appropriate rehabilitation methods lead to improve their problem to use binaural processing skills to successfully suppress background noise and selectively attend to a particular auditory source. This pilot study aims to design a game for auditory training of children with Spatial Processing Disorder (SPD) in Iran and compare their performance in engagement time and speech recognition in noise with those of normal peers. Methods: The game application was designed based on the spatial separation of target and competing stimuli by applying head-related transfer functions. The child's task was to identify the picture of the target word from among the displayed options. Participants were 24 children with SPD and 27 normal peers aged 7-9 years, who performed the speech recognition tasks using the designed game. Results: The game was fascinating and easy to use for most participants. There was no significant difference in mean engagement time between the two groups. The mean engagement time of participants was significantly different between the two groups in terms of age. The children with SPD obtained lower scores in speech recognition in noise tasks. There was no significant difference in speech recognition scores between girls and boys. Conclusion: The designed game application has the potential for speech recognition innoise training of children with SPD in Iran. It is a fascinating and user-friendly tool for simulating the real-life auditory situations for these children.